Pengaruh Profitabilitas dan Sistem Pengendalian Internal Terhadap Audit Delay: Studi Empiris pada Perusahaan Kosmetik yang Terdaftar di Bursa Efek Indonesia Periode 2020-2021 - Rahma Dita Fianti, Finka (CV. Lafadz Jaya, 2024)
This research aims to examine further the factors that influence audit delay. Because an audit that exceeds the statutory deadline will result in a delay in the publication of the financial report which indicates a problem in completing the audit. So, the researchers chose the title